Photophysical and Photoacoustic Properties of Quadrupolar Borondifluoride Curcuminoid Dyes. Issue 4 (14th December 2017) - Bellinger, Stephanie; Hatamimoslehabadi, Maryam; Bag, Seema; Mithila, Farha; La, Jeffrey; Frenette, Mathieu; Laoui, Samir; Szalda, David J.; Yelleswarapu, Chandra; Rochford, Jonathan
Abstract: The synthesis and characterization of a series of donor‐π‐acceptor‐π‐donor (D‐A‐D) curcuminoid molecules is presented herein that incorporates π‐extended aryl and electron‐donating amino terminal functionalization. Computational evaluation shows these molecules possess quadrupolar character with the lowest energy transitions displaying high molar extinction coefficients with broad tunability through manipulation of terminal donating groups. Consistent with their quadrupolar nature, these molecules show varying degrees of solvatochromic behavior in both their absorption and emission spectra, which has been analyzed by Lippert–Mataga and Kamlet–Taft analysis. Photophysical and photoacoustic (PA) properties of these molecules have been investigated by the optical photoacoustic z ‐scan (OPAZ) method. Selected curcuminoid molecules display nonlinear behavior at a high laser fluence through excited state absorption that translates to the production of an enhanced photoacoustic emission. A relative comparison of "molar PA emission" is also presented with the crystal violet linear optical absorbing/linear PA emitting system being utilized as a standard reference material for OPAZ experiments. Furthermore, PA tomography experiments are presented to illustrate the enhanced PA contrast obtainable via an excited state absorption. Abstract : A series of donor‐π‐acceptor‐π‐donor (D‐A‐D) curcuminoid molecules is presented that incorporates π‐extended aryl and electron‐donating amino terminal functionalization.